Household Life Quality And Multidimensional Deprivations In Kwara State, Nigeria - Mohammed, Ojuolape Adebayo (2023)
This study analyses the determinants of key socio-economic issues of out-ofschool children, youth and middle-aged unemployment, and older person's poverty. These three issues are not only peculiar to households but are key components of the United Nations Sustainable Development Goals (SDG). Child schooling falls under SDG4 (quality education), youth unemployment fall under SDG8 (decent work and economic growth), and older person's poverty falls under SDG1 (no poverty). These three issues were further examined to ascertain their collective impact on the household's quality of life. Multinomial logistic regression was used to analyse child schooling enrolment, binary logistic regression for youth and middle-aged unemployment, and older person's poverty. General ordered logistic regression was used to analyse the household quality of life. The study shows that access to school improves child schooling, high cost of education leads to increased out-of-school children, and parents with low educational attainment tend to pay little attention to child schooling. The study shows that many youths and middle-aged household members have no vocational training, and the more they are educated, the more their chances of getting employed.